Effect of body mass index on the efficacy of paracervical block for ultrasound-guided transvaginal oocyte retrieval as assessed by requirement of rescue propofol - Dipti Saxena; Rajeev Rai; Atul Dixit; Shilpa Bhandari; Sadhana Sanwatsarkar (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Oocyte retrieval is the only vital aspect of in vitro fertilization requiring anesthesia. Previous studies have shown the inconclusive role of paracervical block (PCB) in transvaginal oocyte retrieval (TVOR) under ultrasound guidance. This study was planned to observe the role and efficacy of PCB as measured by the amount of propofol used as rescue in patients undergoing TVOR and grading it on the basis of body mass index (BMI). Methods: This prospective, comparative study, conducted over 1 year, recruited 140 American Society of Anesthesiologists I and II patients and divided into two groups as follows: Group A received PCB with 20 ml of 1% lignocaine and Group B received no PCB. Total propofol consumed, BMI, time taken, oocytes retrieved, postprocedure visual analog scale score, and complications were noted. In both the groups, patients were then divided into underweight, normal, overweight, and obese according to BMI. Statistical analysis was done using Statistical Package Mini Tab Version 17.0. The primary objective was to study the efficacy of PCB as estimated by amount of propofol required during the procedure. The secondary aim was to assess the effect of BMI on the efficacy of PCB. Results: Propofol requirement was found to be significantly more (P < 0.05) in Group B patients (172.14 ± 64.15) in comparison to Group A (132.14 ± 66.11). Amount of propofol required in normal BMI and overweight patients was significantly higher in Group B. No significant difference was observed in underweight, and obese patients in both the groups. Conclusion: PCB reduces the consumption of propofol in normal BMI patients. Underweight and obese population do not benefit from PCB.